2022
DOI: 10.1159/000526415
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Damage-Repair Gene Alterations in Genitourinary Malignancies

Abstract: Background High-fidelity repair of DNA damage repair (DDR) [either single-strand- (SSBs) or double-strand breaks (DSBs)] is necessary for maintaining genomic integrity and cell survival. DDR alterations are commonly found in genito-urinary malignancies involving either DSBs repair by the homologous recombination repair (HRR) system (BRCA1/2 pathway) or the SSBs repair through the Poly-ADP-ribose polymerase (PARP) pathway. PARP inhibitors (PARPi) exploit defects in the DNA repair pathway through synthetic letha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The genes of cells are continuously destroyed due to DNA damage [36]. In the lifetime of a cell, naturally occurring DNA damage continues, resulting in SSBs or DSBs [37]. Exogenous factors include IR, UV, and environmental chemicals, and endogenous factors include reactive oxygen species, incorrect DNA replication, accidental ribozyme cleavage, metabolic intermediates [28], erroneous DNA replication, and collapse.…”
Section: Discussionmentioning
confidence: 99%
“…The genes of cells are continuously destroyed due to DNA damage [36]. In the lifetime of a cell, naturally occurring DNA damage continues, resulting in SSBs or DSBs [37]. Exogenous factors include IR, UV, and environmental chemicals, and endogenous factors include reactive oxygen species, incorrect DNA replication, accidental ribozyme cleavage, metabolic intermediates [28], erroneous DNA replication, and collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alterations in the ATM gene are associated with improved overall survival in PC patients treated with olaparib [33]. However, in mCRPC patients treated with olaparib, there was no objective radiological response, in contrast to BRCA1/2 patients [145]. Interestingly, ATM alterations were correlated with better outcomes to cisplatin-based chemotherapy in patients with mCRPC, compared to mCRPC with CDK12 defects [146].…”
Section: Atmmentioning
confidence: 98%
“…Further studies are necessary to confirm these observations. 77 Other new therapies being explored for use in bladder cancer are drugs targeting the androgen receptor (AR), which through different pathways has been linked to the progression and response of this type of cancer. Preclinical studies have shown that AR inhibition in monotherapy can successfully inhibit the growth of urothelial carcinoma and it has a synergistic effect with cisplatin-based chemotherapy.…”
Section: Future Treatment Perspectivesmentioning
confidence: 99%